Myanmar in Eu-Asean relations - Magnus Petersson (2008)
The aim of this paper is to discuss and examine the regional projects of institutionalism in Europe and Southeast Asia. The main focus is on Myanmar, a regional ‘ outcast’ whose membership in the Association of Southeast Asian Nations in 1997 has helped it to gain international legitimacy and be able to stand relatively strong against Western sanctions. The military regime is riding on the wave of ASEAN norms and a communitarian culture. The question remains as to how long the country can continue to do so. A rather skeptical view is emphasized on the ‘ASEAN Way’ in dealing with the military regime, and for the overall political dialogue with the European Union.